The Role of Depression in the Relationship Between Psychological and Physical Intimate Partner Violence. Issue 18 (September 2019) - Barros-Gomes, Patrícia; Kimmes, Jonathan; Smith, Erika; Cafferky, Bryan; Stith, Sandra; Durtschi, Jared; McCollum, Eric
Physical and psychological intimate partner violence (IPV) are significant public health concerns often associated with negative consequences for individuals, families, and society. Because IPV occurs within an interpersonal relationship, it is important to better understand how each partner's depressive symptoms, marital satisfaction, and psychological and physical IPV are interlinked. The purpose of this study was to identify actor and partner effects in a dyadic data analysis association between marital satisfaction and depressive symptoms, its links to psychological IPV, and then to physical IPV. Guided by the social information processing model, this study has implications for understanding the processes leading to various types of IPV in people seeking couples therapy. Using cross-sectional data from 126 heterosexual couples, we conducted an actor–partner interdependence model (APIM) to test actor and partner effects. Indirect actor and partner effects were also assessed. More depressive symptoms were associated with lower marital satisfaction. More depressive symptoms were generally linked with increased perpetration of psychological and physical IPV. Psychological IPV was associated with an individual's use of physical IPV. Effect sizes were moderate to large in magnitude. Four specific indirect effects were identified from depressive symptoms to psychological IPV to physical IPV. Depressive symptoms may be an important factor related to psychological and physical IPV for males and females. Implications include assessing for and treating depression in both partners, and discussing preferred ways of supporting each other that do not include psychological or physical IPV.